PENEGAKAN HUKUM TERHADAP PELAKU USAHA ILLEGAL MINING DALAM PERLINDUNGAN LINGKUNGAN HIDUP DI KONAWE UTARA - Yulian Yusuf, Niken; Kurniawati, Wa Ode Intan; Yusuf, Virya Suprayogi (Jurnal Multidisipliner Bharasumba, 2023)
This research aims 1) To analyze and describe how the environmental impact due to Illegal Mining in North Konawe, 2) To analyze and describe how law enforcement against Illegal Mining business actors in relation to environmental protection in North Konawe. This research will use normative-empirical research, which is a type of research that examines formal legal regulations such as laws and regulations related to the discussion in this thesis such as the 1945 Constitution, Law Number 32 of 2009 concerning environmental protection and management, as well as theoretical concepts which are then linked to their application to law enforcement. The research results show that 1) The conversion of forest function into mining land resulted in deforestation or deforestation in North Konawe. North Konawe experienced deforestation up to 18,155 thousand hectares in 2000-2009, 3,423 hectares in 2009-2013 and reached 17,518 hectares in 2013-2017. FWI stated that the total amount of forest area converted to mining in North Konawe until 2017 was around 152,598 hectares. The loss of forest areas and damage to environmental ecosystems due to illegal mining then caused natural disasters such as floods and landslides which had a direct impact on the surrounding community 2) Law enforcement against Illegal Mining business actors in the perspective of environmental protection to achieve Supremacy Of Law is carried out by applying administrative sanctions, civil sanctions and criminal sanctions. Law enforcement officials in North Konawe carry out law enforcement measures in the form of preventive and repressive efforts including conducting surveillance on every mining activity and efforts to deal with corporate crime.